Rural Market Accessibility and Child School Attendance in Nigeria (Global Business Management Review (GBMR), 2022)
The aim of this study is to examine the effect of market day on child labour participation and school attendance. The data-set of 408 respondents were purposively obtained using structured questionnaire on children 10 to 14 years of age who are residents of Tungan-Mallam rural community, and bivariate probit model was applied. Both the basic theoretical model derived and empirical results shows that, earnings from periodic market activities leads to child participation in labour and reduces their school attendance rate especially on market days. Likewise, even with presence of adult in the household, labour supply on the market day tend to be high due to excessive demand for child labour coupled with lower wage payment when compared to adult wage. The study recommends a strict school attendance especially on the market days with a decisive punishment of class repetition, while general awareness to both parents and children on the danger associated with child labour should be encouraged at intervals.